Obtaining a fermented beverage from cheese whey by using immobilized cells of Kluyveromyces marxianus - Cóndor G., Rocío (2000)
This study has as its main objective the optimization of a technology for the production of a fermented beverage from cheese whey, using Kluyveromyces matxianus and cell immobilization. In a bed packed reactor, the best yield was obtained (11,46±0,81 'GQ with a flux of 140-150 mL.h-1, an immobilized biomass of 10% (v), a column rate of 1/12, a size of pearl of 3 mm of diameter, an addition of sodium metabisulphide (100 pg.mL-1) and immobilized cells with 2% (w/v) of alginate. After the fermentation parameters were optimized in the bioreactor, the alcoholic beverage was inactivated at 70 oC for 5 minutes (thermal treatment) and clarified with "tierra de diatomeas" (1 kg. M-2) . Finally, the alcoholic beverage was evaluated in storage for 6 months, during this period physicochemical, microbiological and sensorial tests were made. Hedonic Scale and Ranking tests showed that the alcoholic beverage had acceptability.